Factors Influencing the New SMEs Decision to Purchase the Product Via Chinese Platform for Shopping : A Case Study of TAOBAO - Kamphangphet, Morakhot; Ratrawetakorn, Teerat; Thaoraktrakul , Bussaba; Sombun, Anchali (Business Administration and Management Journal Review, 2022)
The purpose of this research was to study the attitudes of new entrepreneurs influencing purchasing decisions and online marketing mix (6P) with reference to Taobao platform. The population is based on new entrepreneurs engage in trading business by purchasing products on Taobao platform, using the Stratified Random Sampling method. The sample was collected using a questionnaire from a sample of 400 new entrepreneurs. The analyzed statistics were as follows: descriptive statistics and multiple regression statistics. There is no difference in purchasing decisions on Taobao platform. The monthly income has different purchasing decisions on Taobao platform. The online marketing mix (6P) influences the decision to purchase products on Taobao platform for 3 aspects: Marketing Promotion, Maintain Privacy and Pricing. With regard the attitude factor that influences the decision to purchase on Taobao platform, new entrepreneurs think that in Taobao platform there is a wide variety of products and imported goods will be able to meet the market demand. In the test of attitude factors and online marketing mix (6P) influencing purchasing decisions on Taobao platform, the level of significance was 0.05.